MEMAHAMI KONSEP OIKOS DALAM PERJANJIAN BARU DAN DIALOGNYA DENGAN NILAI PENDIRIAN RUMAH BAGI ORANG BANJAR : (SUATU KAJIAN BIBLIS-KULTURAL) - Sari, May Linda; Ripaldi; Endy (Jurnal Teologi Pambelum, 2024)
This research, which was conducted in March-June 2024 in the city of Banjarmasin, wanted to highlight the meaning of house building for the Banjar people. This research is descriptive in nature and uses critical historical methods on Matthew 7:24-27 to find principles and values ​​that can be dialogued between the biblical and the cultural in terms of building of Banjar houses. Traditionally it is understood that for Banjar people, it does not just function as a place to live because determining the location, selecting building materials, dividing rooms and measuring the building is detailed in detail by considering spiritual and ecological values. Research using theological-cultural studies which combines the theory of historical analysis of texts with a cultural approach, found several research results, namely: first, the foundation has the meaning of life; second, the type of house reflects social strata; third, religious values ​​are the foundation of the house and fourth, ecological values ​​in understanding the house.